Identifying feasible and effective community health worker supervision strategies : experiences of providing and receiving supervision in a rural South African community health worker programme - Stansert Katzen, Sara Linnea (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.